Influence of microscale expansion and contraction caused by thermal and mechanical fatigue on retentive strength of CAD/CAM-generated resin-based composite crowns. (October 2018) - Ankyu, Shuhei; Nakamura, Keisuke; Harada, Akio; Inagaki, Ryoichi; Katsuda, Yusuke; Kanno, Taro; Niwano, Yoshimi; Örtengren, Ulf; Egusa, Hiroshi
Abstract: CAD/CAM-generated resin-based composite crowns have been proposed as an inexpensive alternative to conventional crowns. However, concerns have been raised about crown loosening in clinical use. Therefore, the present in vitro study aimed to evaluate the influence of thermal and mechanical cycling (TC and MC) on retentive strength of CAD/CAM resin-based crowns in relation to microscale expansion and contraction caused by fatigue. Eighty standardized dies were produced using a resin-based composite material. Crowns were milled from resin-based composite (n = 40) and glass-ceramic blocks (n = 40; control) using a dental CAD/CAM system. The crowns bonded to the dies were subjected to TC (temperature: 5 and 55 °C, cycles: 50, 000) and MC (load: 200 N, cycles: 1.2 million). After fatigue treatment, retentive strength of the crowns was evaluated by a crown pull-off test at a crosshead speed of 1 mm/min. Coefficient of thermal expansion (CTE) and modulus of elasticity (E-modulus) of each material were also analyzed to estimate the microscale expansion and contraction during TC and MC. TC and MC significantly reduced the retentive strength of the CAD/CAM resin-based crowns whereas that of the CAD/CAM ceramic crowns was only affected by TC. In addition, the resin-based crowns showed a higher number of crown loosening during TC than the ceramic crowns. Analyses of CTE and E-modulus indicated that the resin-based crowns would be more deformed during TC and MC than the ceramic crowns. The present study demonstrated that the resistance of crowns to microscale expansion and contraction caused by thermal and mechanical fatigue would play an important role in maintaining retentive strength. Graphical abstract: fx1 Highlights: Thermal fatigue decreased the retentive strength of resin-based and ceramic crowns. Mechanical fatigue decreased the retentive strength of resin-based crowns only. Resin-based composite showed higher coefficient of thermal expansion than ceramic. Resin-based composite showed lower modulus of elasticity than ceramic. Microscale expansion caused by fatigue decreases crown retentive strength.